Optimalisasi Formulasi Shampo Herbal Ramah Lingkungan dengan Bahan Alami Daun Randu dan Biji Pepaya - Adelia Rahmawati (Manufaktur: Publikasi Sub Rumpun Ilmu Keteknikan Industri, 2025)
This study aims to develop a natural-based herbal shampoo using Ceiba pentandra (L.) Gaertn leaves and Carica papaya L. seeds as a safer and eco-friendly alternative to synthetic shampoos, which often contain harmful chemicals. Ceiba pentandra leaves contain active compounds such as flavonoids, alkaloids, and saponins with antibacterial properties, while Carica papaya seeds contain glucoside circirindan, which is beneficial for treating gray hair. The research method involves the use of influence diagrams and mathematical models to determine the most effective ingredient formulation. The experimental results showed that the best composition consists of 60 grams of Ceiba pentandra leaves, 30 grams of Carica papaya seeds, 5 grams of texavon, 10 grams of NaCl, and 350 ml of distilled water. The resulting herbal shampoo product is not only effective and economical but also environmentally friendly.